Etude théorique de l’énergie de formation et de cohésion du matériau N2BaSr et ses applications industrielles. - BENSAID, Mohamed (faculté des sciences et technologie, 2022)
Les propriétés structurelles, électroniques et magnétiques du composé fullHeusler : N2BaSr vont être calculé par la méthode des ondes planes augmentées (FPLAPW) qui se base sur la théorie de la fonctionnelle de la densité (DFT) en utilisant le code de Wien2K. Nous avons utilisé l'approximation du gradient généralisé (GGA(06)) pour le terme du potentiel d'échange et de corrélation (XC).A large number of researches who is interested on the class of half-metallic ferromagnets HMF like transition metal oxides, Heusler alloys and manganites. The existence of HMF is marked from its band structure. In full-Heusler compounds X2YZ, where X and Y represent two different transition metals (or a transition (T) metal with a rare earth (RE) metal), and Z represents a p element of the 3rd, 4th, or 5th main group. The study will be carried out using the linearized augmented plane waves method with total potential (FP-LAPW) based on the density functional theory (DFT), implemented in the Wien2k code. The energy of exchange and correlation is described by the generalized gradient approximation (GGA) of Perdew, Burk and Ernzerhof. The crystal structure of the N2BaSr compound as well as its band structure and its electronic state density will be investigated. ملخص : تعاظم في الآونة الحالية الاهتمام بالمغناطيس في بعض المواد ه س ل روالتي لها تطبيقات هامة في مجال أجهزة الالكترونيات الدوارنية . بواسطة طريقة الأمواج المستوية خطيا FP-LAPWوالتي ترتكز على نظرية الكثافة الدالية DFTمدمجة ضمن برنامج WIEN2Kقمنا بحساب الخصائص البنيوية , الالكترونية , المغناطيسية ,المطاطية للمركب ) (N2BaSrعن طريق هذه النظرية, قمنا باستعمال تقريب التدرج المعمم PBE-GGA لأجل حساب كمون التبادل – الارتباط ( )XCبغية حساب الخصائص البنيوية والإلكترونية المراد معرفتها:وسيط الشبكة ،معامل الانضغاط وعصابات الطاقة .وانتهينا بمقارنة التنبؤات الأولية بالنتائج المحققة بالأعمال النظرية المتعلقة بها .وقد وجد أن العزم المغناطيسي في هذ المركب يساوي عدد كامل .
Keywords: Demi-metal, propriétés magnétiques, GGA-PBE, DFT, ferromagnétique